Tolérance et transgressivité : le jeu à somme nulle des gauchistes et des islamistes tunisiens - Michaël Béchir Ayari (L’Année du Maghreb)
From the 1960s to the 1990s, the cycle of protest followed by Islamist challenge has brought a number of Tunisians before the courts. During this period, the authoritarian state allowed some form of opposition while repressing another. In this sense, the 2000s look like the 1980s. Indeed, between 1979 and 1981 leftists were effectively amnestied while political Islam was suppressed for the first time. Moreover, in mid 2000s, the release of jailed Ennhada militants and the return of exiled activists suggest that a protest cycle of a new kind is under way. This article analyzes leftist tendencies and Tunisian Islamism especially in terms of the modalities of activist political socialization. Its purpose is to recall that these two forms of opposition have succeeded against transgressive behaviour, exchanging tolerance and disobedience. The paper further advances the hypothesis in the 2000s, the Tunisian state is seeking allies to face a new enemy, a trend which is in many ways difficult to observe.